2016
DOI: 10.1109/mcom.2016.7509376
|View full text |Cite
|
Sign up to set email alerts
|

The TUCAN3G project: wireless technologies for isolated rural communities in developing countries based on 3G small cell deployments

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 10 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…The results obtained from the pilot showed that the solution proposed by TUCAN3G was technically and economically viable in the medium term, since the reduction of costs achieved allowed for the maintenance of the network with the income of small communities [13]. However, these studies also showed that the income obtained was not sufficient to compensate the investment required in jungle environments, therefore it was still necessary to look for subsidies to scale this type of solution to other regions and ensure sustainability in the long term.…”
Section: Economic Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained from the pilot showed that the solution proposed by TUCAN3G was technically and economically viable in the medium term, since the reduction of costs achieved allowed for the maintenance of the network with the income of small communities [13]. However, these studies also showed that the income obtained was not sufficient to compensate the investment required in jungle environments, therefore it was still necessary to look for subsidies to scale this type of solution to other regions and ensure sustainability in the long term.…”
Section: Economic Sustainabilitymentioning
confidence: 99%
“…The TUCAN3G project, funded by the European Commission, tried to fill this gap in the quest for solutions to connect the unconnected, and successfully deployed pilots of 3G cellular networks in remote areas involving an MNO [12,13]. TUCAN3G marked the guidelines for making alliances with different stakeholders that seek more sustainable and scalable rural telecommunications networks with the participation of an MNO, an experience that should be seen as complementary to the also successful experiences of bottom-up initiatives with a strong emphasis on the role of communities.…”
Section: State Of the Art In Telecommunications Infrastructures And Smentioning
confidence: 99%
“…Wireless networks are the preferred path investigated for finding a solution to the problem by many researchers, using ad hoc [2] or Wi-Fi based [3] networks. The economic feasibility of these solutions has also been studied by certain researchers [3] [4] [5].…”
Section: Literature Surveymentioning
confidence: 99%
“…Wireless networks are the preferred path investigated for finding a solution to the problem by many researchers, using ad hoc [2] or Wi-Fi based [3] networks. The economic feasibility of these solutions has also been studied by certain researchers [3] [4] [5]. Partnership-based models have generally been proposed to lower the costs of project implementation as well as make the solution affordable for consumers [4] [5].…”
Section: Literature Surveymentioning
confidence: 99%
“…For providing 3G and 4G connectivity, one of the most cost‐effective approaches is to use shared low‐cost private infrastructures where the operator offers services adjusted to the real needs of the target population . These infrastructures may consist of an heterogeneous wireless backhaul (BH) network that interconnects a number of small cells deployed as access networks (ANs).…”
Section: Introductionmentioning
confidence: 99%